Ballistic tracks in graphene nanoribbons. Issue 1 (December 2018) - Aprojanz, Johannes; Power, Stephen; Bampoulis, Pantelis; Roche, Stephan; Jauho, Antti-Pekka; Zandvliet, Harold; Zakharov, Alexei; Tegenkamp, Christoph
Abstract High quality graphene nanoribbons epitaxially grown on the sidewalls of silicon carbide (SiC) mesa structures stand as key building blocks for graphene-based nanoelectronics. Such ribbons display 1D single-channel ballistic transport at room temperature with exceptionally long mean free paths. Here, using spatially-resolved two-point probe (2PP) measurements, we selectively access and directly image a range of individual transport modes in sidewall ribbons. The signature of the independently contacted channels is a sequence of quantised conductance plateaus for different probe positions. These result from an interplay between edge magnetism and asymmetric terminations at opposite ribbon edges due to the underlying SiC structure morphology. Our findings demonstrate a precise control of transport through multiple, independent, ballistic tracks in graphene-based devices, opening intriguing pathways for quantum information device concepts. Electronic highways were realized by means of epitaxially grown graphene nanoribbons on SiC substrates. Here, the authors use spatially-resolved two-point probe and conductive AFM measurements, supplemented by tight-binding calculations, to image the one-dimensional ballistic transport channels.